Ginsenoside Rg3 Alleviates Cisplatin Resistance of Gastric Cancer Cells Through Inhibiting SOX2 and the PI3K/Akt/mTOR Signaling Axis by Up-Regulating miR-429 - Wang, Xiaofeng; He, Rui; Geng, Li; Yuan, Jing; Fan, Huijie (Frontiers in Genetics, 2022)
Background: We aimed to reveal whether Ginsenoside Rg3 alleviates cisplatin resistance and sensitizes gastric cancer (GC) cells to cisplatin-induced apoptosis and draw out the underlying molecular mechanism in cisplatin-resistant GC cells. Results: The lower expression of miR-429 was found in association with cisplatin-resistance in GC cells and expression of which was restored following Ginsenoside Rg3 treatment. SOX2 was found to contribute to developing platinum-resistance and was a target for miR-429 in AGSR-CDDP cells. Importantly, enforced expression of SOX2 with a pcDNA3-SOX2 construct lacking the 3’-UTR miRNA binding site diminished the cytotoxic effects of miR-429 in AGSR-CDDP cells. We demonstrated that Ginsenoside Rg3 enhanced chemosensitivity in AGSR-CDDP GC cells, at least in part, through up-regulating miR-429, thereby targeting SOX2 and modulating downstream PI3K/AKT/mTOR signaling. Ginsenoside Rg3 was also found to regulate apoptosis-related genes via miR-429 in cisplatin-resistant GC cells. Ginsenoside Rg3 significantly suppressed AGSR-CDDP cell migration, while following transfection with anti-miR-429, the anti-migratory effects of Ginsenoside Rg3 was partially abolished. Conclusions: We concluded that miR-429-regulated SOX2 expression is one of the main mechanisms by which Ginsenoside Rg3 dramatically promotes its anticancer effects on cisplatin-resistant GC cells. We underscored a supporting model in which miR-429 adjusts PI3K/AKT/mTOR signaling by regulating SOX2 in cisplatin-resistant GC cells.